2015
DOI: 10.1089/thy.2015.0039
|View full text |Cite|
|
Sign up to set email alerts
|

Geospatial and Temporal Analysis of Thyroid Cancer Incidence in a Rural Population

Abstract: Background: The increasing incidence of thyroid cancer has resulted in the rate tripling over the past 30 years. Reasons for this increase have not been established. Geostatistics and geographic information system (GIS) tools have emerged as powerful geospatial technologies to identify disease clusters, map patterns and trends, and assess the impact of ecological and socioeconomic factors (SES) on the spatial distribution of diseases. In this study, these tools were used to analyze thyroid cancer incidence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…This may help to explain why the largest increase in incidence has occurred in the 20-50 year age group rather than in older women. 49 Other authors have suggested race, ethnicity, and nativity as contributing factors. [50][51][52][53][54][55] In Sweden, immigrants from the middle east, Asia, and South America have an increased incidence of well-differentiated thyroid cancer, 56 and in New Zealand, women from Pacific regions have a higher incidence in comparison with women of European descent.…”
Section: Sex and Ethnic Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…This may help to explain why the largest increase in incidence has occurred in the 20-50 year age group rather than in older women. 49 Other authors have suggested race, ethnicity, and nativity as contributing factors. [50][51][52][53][54][55] In Sweden, immigrants from the middle east, Asia, and South America have an increased incidence of well-differentiated thyroid cancer, 56 and in New Zealand, women from Pacific regions have a higher incidence in comparison with women of European descent.…”
Section: Sex and Ethnic Differencesmentioning
confidence: 99%
“…Hall et al found a 3‐fold increase in the use of diagnostic imaging in women in comparison with men, and the largest increase occurred in young women. This may help to explain why the largest increase in incidence has occurred in the 20‐50 year age group rather than in older women …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid cancer is one of the most frequent types of endocrine neoplasms worldwide, with ~300,000 new cases occurring every year (1,2). Due to several environmental and socioeconomic factors, the occurrence rate of thyroid cancer is more increased among rural populations (3). Thyroid cancer has been identified as one of the most common types of malignancy among Asian population in 2015 (4).…”
Section: Introductionmentioning
confidence: 99%
“…Several informatics methods have investigated environmental perturbations and their effects on human health and disease. Studies have used Electronic Health Record (EHR) data to investigate environmental challenge in disease progression, 3 identified thyroid cancer hotspots in Vermont, 4 and correlated air pollution with disease risk in Italy. 5 Environment-Wide Association Studies have been performed using EHR data.…”
Section: Introductionmentioning
confidence: 99%